2021
DOI: 10.3390/ijms22031341
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6-Selective Inhibitor Overcomes Bortezomib Resistance in Multiple Myeloma

Abstract: Although multiple myeloma (MM) patients benefit from standard bortezomib (BTZ) chemotherapy, they develop drug resistance, resulting in relapse. We investigated whether histone deacetylase 6 (HDAC6) inhibitor A452 overcomes bortezomib resistance in MM. We show that HDAC6-selective inhibitor A452 significantly decreases the activation of BTZ-resistant markers, such as extracellular signal-regulated kinases (ERK) and nuclear factor kappa B (NF-κB), in acquired BTZ-resistant MM cells. Combination treatment of A45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
(34 reference statements)
1
10
0
Order By: Relevance
“…In addition, looking for novel therapeutic agents is an alternative to overcome bortezomib resistance. It is worth mentioning that previous reports and our research confirmed that BTZ-resistant MM cells have an enhanced activation of the MAPK/ERK pathway ( Lee et al, 2021 ). Thus, we subsequently analyzed whether SHP2 inhibitors could be effective against BTZ-resistant MM cells.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, looking for novel therapeutic agents is an alternative to overcome bortezomib resistance. It is worth mentioning that previous reports and our research confirmed that BTZ-resistant MM cells have an enhanced activation of the MAPK/ERK pathway ( Lee et al, 2021 ). Thus, we subsequently analyzed whether SHP2 inhibitors could be effective against BTZ-resistant MM cells.…”
Section: Discussionsupporting
confidence: 84%
“…The discussions about the side effects and improvement of therapeutic strategies have led to the development of HDAC isoform-selective inhibitors to overcome undesired effects [316]. Until now, most of the agents developed have selectivity for HDAC3, HDAC6 and HDAC8 and have been or are still currently evaluated in preclinical studies for cancer and lung fibrosis [171,189,[234][235][236][237][238]258]. However, numerous HDACs have the very same targets.…”
Section: Discussion Of Hdac Inhibitors As Therapeutic Option For Ipfmentioning
confidence: 99%
“…In addition, HDAC6 plays a vital role in the proteolysis pathway of misfolded proteins as it deacetylates α-tubulin for induction of aggresome formation, in which (cytotoxic) ubiquitylated protein aggregates are sequestered for lysosomal degradation and autophagic clearance, thereby attenuating ER stress [187]. HDAC6-dependent autophagy is considered to confer malignancy and aggressiveness to cancer cells and is linked to resistance to proteasome inhibitors (e.g., bortezomib) in patients with various cancers [189]. In addition, HDAC6 is implicated in metastasis formation through the induction of TGF-β-dependent epithelial-mesenchymal transition (EMT) [190,191].…”
Section: The Hdac Family/hdac Classes and Their Function-lessons From...mentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with 5-Fu, WT161 synergistically inhibited osteosarcoma cells both in vitro and in vivo by increasing the level of PTEN [ 53 ]. HDAC6-selective inhibitor A452 can enhance sensitivity of acquired bortezomib (BTZ)-resistant multiple myeloma cells to bortezomib by inhibiting the activation of ERK and NF-κB in [ 64 ]. The combination of imatinib, a tyrosine kinase inhibitor, and the HDAC6 inhibitor 7b was shown to synergistically induce caspase-dependent apoptotic cell death and decrease the proportion of leukemia stem cells [ 65 ].…”
Section: Hdac6-selective Inhibitorsmentioning
confidence: 99%